Ethnomedicinal survey and scientific validation of inflammation-healing plants used by the Tengger community in East Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Bhagawan WS, Ekasari W, Agil M. 2025. Ethnomedicinal survey and scientific validation of inflammation-healing plants used by the Tengger community in East Java, Indonesia. Biodiversitas 26: 3160-3173. This study investigates the profound ethnomedicinal knowledge of the Tengger community in East Java, Indonesia, with a specific focus on plant species traditionally used to manage inflammation and pain-related conditions. The primary objective was to meticulously document the medicinal plants utilized by the community and assess their pharmacological relevance through literature-based validation. Data were obtained through semi-structured interviews and in-depth observations with selected informants, using a snowball sampling technique. Quantitative indices (species use value, family use value, fidelity level, and informant consensus factor) were applied to evaluate each species' cultural and therapeutic significance. A total of 82 plant species belonging to 42 families were identified and utilized in various preparations to treat 15 inflammation and pain-related disorders. Notably, 4 of the 6 plant species with the highest species use value have been scientifically validated for their anti-inflammatory and analgesic activities, providing a solid foundation for the community's traditional knowledge. However, the pharmacological properties of Borreria laevis and Elaeocarpus longifolius remain unexplored. The enduring use of these medicinal plants is a testament to the community's rich ethnomedical tradition, and further pharmacological investigations may lead to the discovery of new therapeutic agents for treating inflammation and pain.
Keywords: Ethnomedicine, inflammation, medicinal plants, Tengger community